The Relevance of The Principle of No Criminal Punishment Without Fault (Geen Straf Zonder Schuld) in Corporate Criminal Liability in Indonesia - Kurdi, Kurdi; Ardhan, Adery; Dadek, Teuku Ahmad (JURNAL MERCATORIA, 2025)
The principle of Geen Straf Zonder Schuld faces a paradox when applied to corporations, which, as a legal fiction, have no mens rea. However, the profound impact of corporate crime demands an effective mechanism for criminal accountability. This normative juridical research examines the relevance of the principle of Guilt in Indonesian corporate criminal Law through legislative, conceptual, and case-based approaches. The first findings show that, before the New Criminal Code, the application of the principle of Guilt was pragmatic through the Theory of Identification, which attributed the corporation's mens rea to the management or directing mind. This approach is supported by PERMA No. 13 of 2016 and is evident in decisions such as PT GJW and PT CND. The second finding shows the evolution of the doctrine in two directions: (a) the exclusion of the principle of culld through strict Liability in various lex specialis, especially the Law on Environmental Protection and Management; and (b) the transformation of the meaning of debt through the Corporate Culture Model, which views blame as the failure of the system or organizational culture to prevent crime. The culmination is the codification of the Corporate Culture Model in the New Criminal Code (Law No. 1 of 2023), which marks a shift from treating mistakes as lending errors to treating them as authentic corporate mistakes.